SNAP Decisions: Qualitative Research on the Perceived Influence of the COVID-19 Pandemic and Supplemental Nutrition Assistance Program Benefit Changes on Food Purchases - C. Ross Hatton; Jessica Eller; Denise Simon; Melanie Caldwell; Alexandra Ross; Anne N. Thorndike; Eric B. Rimm; Joshua Petimar; Michele Polacsek (Journal of the Academy of Nutrition and Dietetics, 2026)

Corrigendum to ‘Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control’ [Aquaculture Volume 622 15 July 2026 744046] - Jessica Hintzsche; Lorenzo Vincenzo Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control - Jessica Hintzsche; Lorenzo V. Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly S. Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

Beef quality grading using rapid evaporative ionization mass spectrometry (REIMS) - Yafang Cui; Lynda S. Perkins; Jingjing Liu; Alastair B. Ross; Jingyao Wang; Wenyang Jia; Ezequiel Jorge-Smeding; Alix Neveu; Isabelle Legrand; Marie-Pierre Ellies-Oury; Nigel D. Scollan; Jean-Francois Hocquette (Meat Science, 2026)

Prenatal exposure to gas stoves, mold, and water damage: Associations with gestational duration and fetal growth in the ECHO cohort - Jiwon Oh; Lesliam Quirós-Alcalá; Mohamad Burjak; Anna J. Ross; Lisa A. Croen; Aisha S. Dickerson; Assiamira Ferrara; Rima Habre; Irva Hertz-Picciotto; Margaret R. Karagas; Christine T. Loftus; Rebecca J. Schmidt; et al. (Environmental Pollution, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Calibration of the species threat abatement and restoration metric's threat abatement component in a Costa Rican landscape - Louise Mair; Thomas M. Brooks; Randall R. Jimenez; Nicholas B. W. Macfarlance; Tony Nello; Antonin Vergez; Leon Bennun; Florence Curet; Annie Dakmejian; Edward Ellis; Melibea Gallo; Philip J. K. McGowan; et al. (Conservation Biology, 2026)
Achieving global conservation policy goals requires the ability to set and measure progress toward science‐based targets for biodiversity. The species threat abatement and restoration (STAR) metric was developed to enable actors to set science‐based targets for species. STAR scores quantify the potential contribution of actions to abate threats and restore habitat to reduce species extinction risk in a particular place and can be aggregated and disaggregated among species, threats, and areas of interest. Estimated STAR scores are based on data from the International Union for Conservation of Nature Red List and provide initial information on the species and threats expected to be present in an area. Operationalization of the metric requires verification of the presence of species and the presence and severity of threats in the area to inform calculation of a calibration STAR score. We applied a pilot calibration process for the threat abatement component of STAR (STAR T ) in the San Jose northern subcatchments landscape in Costa Rica. We used specialist knowledge and geospatial analyses of habitat loss to determine the species present and the intensity of threats affecting them in the landscape. Calibration yielded a more even distribution of scores among threats than was apparent from estimated STAR T and identified that reducing the threat from livestock farming and ranching had the greatest potential to reduce species extirpation risk. Calibration also showed that there is an opportunity to prevent the extinction of a critically endangered endemic amphibian, but the species’ presence requires confirmation. The pilot demonstrated how specialist knowledge and geospatial analyses can be combined during calibration to produce a calibrated STAR T score capable of informing science‐based targets for species conservation. Our calibration process can be applied to other areas.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Dual potential of tetrandrine: Antiangiogenic efficacy and safety liabilities revealed through in silico, in vitro, and zebrafish models - Shaira Shane M. Orencio; Oliver B. Villaflores; Ferry Saputra; Gilbert Audira; Chung-Der Hsiao; Ross D. Vasquez (Food and Chemical Toxicology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Revised PVT equations of state for almandine and spessartine garnets: implications for piezobarometry - Ross J. Angel; Marta Morana; Sergio Speziale; Nicola P. M. Casati; Alan B. Woodland; Matteo Alvaro; Guy L. Hovis; Mario Tribaudino (Contributions to Mineralogy and Petrology, 2026)

Impact of freshwater rearing on saltwater performance: A genotype-environment interaction study in Atlantic Salmon (Salmo salar) - Mette J. Tollervey; Saif Agha; Michaël Bekaert; Almas A. Gheyas; Ross D. Houston; Andrea Doeschl-Wilson; Ashie Norris; Herve Migaud; Alejandro P. Gutierrez; Monica B. Betancor (Aquaculture, 2026)

Stad Slide: Preconditioning and failure of one of the world's largest megaslides - B. K. Tiller; C. L. Batchelor; B. Bellwald; B. Manton; K. Winter; N. Ross; S. Planke (Journal of Quaternary Science, 2025)
Submarine landslides can generate tsunamis and pose risks to underwater infrastructure, but a lack of direct observations of such slides hinders our understanding of their development and hazard potential. Studying the morphology of past slides can offer insights into their preconditioning and failure. Here, new high‐quality 2D and 3D seismic data were used to determine, for the first time, the extent and morphology of the Stad Slide (~0.4 Ma) on the northeast Atlantic margin. With a volume of ~4300 km 3 and a maximum thickness of ~360 m, we reveal that this slide is the largest by volume on the proximal North Sea Fan and amongst the largest known megaslides globally. Its large volume was likely facilitated by retrogressive development along layers of glacimarine and contouritic sediment. The broad timing of the Stad Slide aligns with enhanced glacial sedimentation in this region, which is likely to have preconditioned failure by increasing overpressure in underlying sediments. The slide headwalls are infilled by an ~200 m‐thick contourite drift that may have formed the weak layer for subsequent sliding on the North Sea Fan.

Elastic thermobarometry of natural and experimental quartz inclusions in garnet (QuiG) under tension - Joseph P. Gonzalez; Mattia L. Mazzucchelli; Jay B. Thomas; Ross J. Angel; Robert S. Darling; Khi X. Atchinson; Mattia Gilio; Matteo Alvaro (Contributions to Mineralogy and Petrology, 2025)

Ovarian superstimulation for in vitro embryo production based on Anti-Müllerian hormone phenotype: Effect of FSH dose schedule - Jessica C.L. Motta; Rodrigo V. Sala; Cameron B. Hayden; Daniela C. Pereira; Vanessa C. Fricke; Victor A. Absalón-Medina; Pablo J. Ross; Alvaro García-Guerra (Animal Reproduction Science, 2025)

Spatial distribution and source apportionment of polycyclic aromatic hydrocarbons (PAHs) in surficial sediments along the coast of British Columbia, Canada - Elizabeth J. Ruberg; Mark B. Yunker; Gabriela Aguirre-Martinez; Kelsey Delisle; Carmen Morales-Caselles; Peter S. Ross; Marie Noël (Marine Pollution Bulletin, 2025)

Human perceptions and reports of pro-environmental behaviours in the context of plastic pollution in rural communities within a UNESCO subtropical biosphere reserve - Ronald Mashamba; Mwazvita T. B. Dalu; Ross N. Cuthbert; Farai Dondofema; Tatenda Dalu (Journal of Environmental Studies and Sciences, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Long‑term monitoring of mercury in Vermont’s forest soils: trends over 20 years in near–surface horizons - Donald S. Ross; James B. Shanley; Angelica T. Quintana; Thomas R. Villars; Joshua M. Halman; Scott W. Bailey; Jennifer A. Bower (Environmental Monitoring and Assessment, 2025)

Do soil enzymes respond to silvicultural management? - Fernanda C.C. Oliveira; Allan Bacon; Thomas R. Fox; Eric J. Jokela; Michael B. Kane; Timothy A. Martin; Asko Noormets; C. Wade Ross; Jason Vogel; Daniel Markewitz (Forest Ecology and Management, 2025)

Heat-tolerant algal symbionts may prevent extirpation of the threatened elkhorn coral, Acropora palmata, in Florida during intensifying marine heatwaves - Richard F. Karp; Fabrizio Lepiz-Conejo; Shayle B. Matsuda; Bryce Corbett; Alexandra D. Wen; Joseph D. Unsworth; Martine D’Alessandro; Ken Nedimyer; Amelia Moura; Erinn M. Muller; Zachary Craig; Diego Lirman; et al. (Coral Reefs, 2025)
The elkhorn coral, Acropora palmata , was historically a major reef-building species in the Caribbean, but has suffered devastating declines in recent decades. Despite significant restoration efforts in Florida, the marine heatwave of 2023 caused severe bleaching and mortality to both wild and restored colonies. To understand the disastrous impacts, we evaluated the variation in heat tolerance among Florida’s A. palmata population prior to the event. In 2022, we used rapid acute heat stress assays to assess the thermal tolerance of 172 adult colonies (125 unique genets) from four nurseries. We found variation in thermal tolerance (4.17°C range in ED50) that was attributed to nursery location (17.2% of variation), genet (25.9%), and symbiont abundance (15.6%). Algal symbiont type, however, was the strongest predictor of thermal performance, with the few (n = 10) colonies hosting Durusdinium being, on average, 1.9°C more thermally tolerant than corals hosting Symbiodinium . This difference would have decreased the effective heat stress accumulation during the 2023 event by ~92%. Therefore, despite considerable variation in thermal tolerance among Florida’s elkhorn corals, hosting Durusdinium appears to be the most effective mechanism for surviving such extreme heat stress. These findings suggest that restoration strategies that focus on rearing sexually derived A. palmata recruits with Durusdinium , followed by outplanting to suitable environments, may improve survival during future heatwaves. Combined with efforts to introduce additional elkhorn diversity from populations outside Florida, these approaches may be the most effective interventions to promote the continued survival of Florida’s elkhorn corals in the face of rapid climate change.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

“Hope at a better chance”: perspectives on genetic counseling and testing among black individuals with prostate cancer - Breanne Prindeville; Brittany M. Szymaniak; Samantha E. Greenberg; Adam B. Murphy; Ashley E. Ross; Debra Duquette (Journal of Community Genetics, 2025)

Bioeconomic modeling of on-growing Caribbean spiny lobster in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Sherry Larkin; Thomas R. Matthews; Erica Ross (Aquaculture, 2025)

Evaluating the role of binge planning and binge inevitability within affect regulation models of binge eating - Glen Forester; Lauren M. Schaefer; Jeffrey S. Johnson; Brianne N. Richson; Robert D. Dvorak; Ross D. Crosby; Carol B. Peterson; Stephen A. Wonderlich (Appetite, 2024)

Jaw-muscle fiber architecture and skull form facilitate relatively wide jaw gapes in male cercopithecoid monkeys - Andrea B. Taylor; Claire E. Terhune; Callum F. Ross; Christopher J. Vinyard (Journal of Human Evolution, 2024)

Food system adaptation and maintaining trade could mitigate global famine in abrupt sunlight reduction scenarios - Morgan Rivers; Michael Hinge; Kevin Rassool; Simon Blouin; Florian U. Jehn; Juan B. García Martínez; Vasco Amaral Grilo; Victor Jaeck; Ross J. Tieman; James Mulhall; Talib E. Butt; David C. Denkenberger (Global Food Security, 2024)

On the use of rapid acute heat tolerance assays to resolve ecologically relevant differences among corals - Ross Cunning; Shayle B. Matsuda; Erich Bartels; Martine D’Alessandro; A. Raine Detmer; Pierrick Harnay; Jessica Levy; Diego Lirman; Holly V. Moeller; Erinn M. Muller; Ken Nedimyer; Ferdinand Pfab; et al. (Coral Reefs, 2024)

A quantitative modeling framework to understand the physiology of the hypothalamic-pituitary-adrenal axis and interaction with cortisol replacement therapy - Davide Bindellini; Robin Michelet; Linda B. S. Aulin; Johanna Melin; Uta Neumann; Oliver Blankenstein; Wilhelm Huisinga; Martin J. Whitaker; Richard Ross; Charlotte Kloft (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Congenital adrenal hyperplasia (CAH) is characterized by impaired adrenal cortisol production. Hydrocortisone (synthetic cortisol) is the drug-of-choice for cortisol replacement therapy, aiming to mimic physiological cortisol circadian rhythm. The hypothalamic-pituitary-adrenal (HPA) axis controls cortisol production through the pituitary adrenocorticotropic hormone (ACTH) and feedback mechanisms. The aim of this study was to quantify key mechanisms involved in the HPA axis activity regulation and their interaction with hydrocortisone therapy. Data from 30 healthy volunteers was leveraged: Endogenous ACTH and cortisol concentrations without any intervention as well as cortisol concentrations measured after dexamethasone suppression and single dose administration of (i) 0.5–10 mg hydrocortisone as granules, (ii) 20 mg hydrocortisone as granules and intravenous bolus. A stepwise model development workflow was used: A newly developed model for endogenous ACTH and cortisol was merged with a refined hydrocortisone pharmacokinetic model. The joint model was used to simulate ACTH and cortisol trajectories in CAH patients with varying degrees of enzyme deficiency, with or without hydrocortisone administration, and healthy individuals. Time-dependent ACTH-driven endogenous cortisol production and cortisol-mediated feedback inhibition of ACTH secretion processes were quantified and implemented in the model. Comparison of simulated ACTH and cortisol trajectories between CAH patients and healthy individuals showed the importance of administering hydrocortisone before morning ACTH secretion peak time to suppress ACTH overproduction observed in untreated CAH patients. The developed framework allowed to gain insights on the physiological mechanisms of the HPA axis regulation, its perturbations in CAH and interaction with hydrocortisone administration, paving the way towards cortisol replacement therapy optimization. Graphical Abstract

Assessing the ecological functioning and biodiversity of remnant native flat oyster (Ostrea angasi) reefs in temperate southeast Australia - Elisabeth M.A. Strain; Ana B. Bugnot; Boze Hancock; Robinson W. Fulweiler; Donald J. Ross; Simon E. Reeves (Marine Environmental Research, 2024)

Reflex impairment as a predictor of mortality in Panulirus argus: Implications for the live export market - Erica P. Ross; Casey B. Butler; Carly M. Hannah; Thomas R. Matthews (Fisheries Research, 2024)

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Performing food safety inspections - Jason B. Barnes; James C. Smith; Kirstin E. Ross; Harriet Whiley (Food Control, 2024)

Price variation in the Caribbean spiny lobster fishery: Incentives for ongrowing wild-caught lobsters in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Thomas R. Matthews; Erica Ross (Fisheries Research, 2024)

Blanford's fox (Vulpes cana) habitat suitability in Saudi Arabia: Insights from camera trapping and ensemble species distribution modelling - J. Philip B. Faure; Marine Drouilly; Alexander E. Botha; Michael D. Ross; J. Andrew Spalton; Mesfer AlHlafi; Carolyn E. Dunford; David R. Mills; Ross De Bruin; Emma Gallacher; Gareth K.H. Mann (Journal of Arid Environments, 2024)

Fatty acid profiles and stable isotope composition of Antarctic macroalgae: a baseline for a combined biomarker approach in food web studies - Ross Whippo; Katrin Iken; Charles D. Amsler; Alexander T. Lowe; Julie B. Schram; Andrew G. Klein; Sabrina Heiser; Margaret O. Amsler; James B. McClintock; Aaron W. E. Galloway (Polar Biology, 2024)
The Western Antarctic Peninsula supports a diverse assemblage of > 100 described macroalgal species that contribute to the base of coastal food webs, but their contribution to local nearshore food webs is still uncertain across larger spatial scales. The analysis of biomarkers, specifically fatty acids and stable isotopes, offers a tool to clarify the trophic role of Antarctic macroalgae. The aim of this study was to describe the fatty acid profiles and stable isotope values of 31 algal species from three divisions (Chlorophyta—1, Ochrophyta—8, Rhodophyta—22) collected at the same sites for both biomarkers. Of these, 13 species had no previously published fatty acid profiles. Most species were rich in polyunsaturated fatty acids (PUFAs), suggesting they are highly nutritious and could be a resource of essential fatty acids for consumers. This was specifically noticeable in the overall low PUFA ratio (∑ω6/∑ω3 ratio), with low ratios being an indicator of high nutritional quality for consumers. Fatty acid profiles of macroalgae grouped strongly by phylogeny (at the levels of division, order, and family), while stable isotope groupings were more driven by the physiological properties of the species. Specifically, some closely related red algal species exhibited very different stable isotope values based on their carbon concentrating mechanisms, with highly 13 C-depleted values in several Rhodophyta species. The fact that the two biomarker approaches created different groupings of Antarctic macroalgae collected at the same locations emphasizes that their combined application can be a powerful tool in Antarctic coastal food web studies.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Complexity-functioning relationships differ across different environmental conditions - Mariana Mayer-Pinto; Amelia Caley; Antony M. Knights; Laura Airoldi; Melanie J. Bishop; Paul Brooks; Ricardo Coutinho; Tasman Crowe; Paolo Mancuso; Lais P.D. Naval-Xavier; Louise B. Firth; Rafael Menezes; et al. (Journal of Environmental Management, 2024)

Characterising ecological resource utilization by the endangered Egyptian vulture in Oman to better manage and mitigate electrocution risk - M.J. McGrady; S. Ross; M.H. AlJahdhami; B.-U. Meyburg (Journal for Nature Conservation, 2024)

Oceanic mantle beneath ultraslow spreading ridges metasomatized by variably evolved melts - Wei-Qi Zhang; Chuan-Zhou Liu; Henry J. B. Dick; Ross N. Mitchell; Bo-Da Liu (Contributions to Mineralogy and Petrology, 2024)

First evaluation of stiff-in-soft host–inclusion systems: experimental synthesis of zircon inclusions in quartz crystals - Joseph P. Gonzalez; Jay B. Thomas; Mattia L. Mazzucchelli; Ross J. Angel; Matteo Alvaro (Contributions to Mineralogy and Petrology, 2024)
Quartz crystals with zircon inclusions were synthesized using a piston-cylinder apparatus to experimentally evaluate the use of inclusions in “soft” host minerals for elastic thermobarometry. Synthesized zircon inclusion strains and, therefore, pressures ( P inc ) were measured using Raman spectroscopy and then compared with the expected inclusion strains and pressures calculated from elastic models. Measured inclusion strains and inclusion pressures are systematically more tensile than the expected values and, thus, re-calculated entrapment pressures are overestimated. These discrepancies are not caused by analytical biases or assumptions in the elastic models and strain calculations. Analysis shows that inclusion strain discrepancies progressively decrease with decreasing experimental temperature in the α-quartz field. This behavior is consistent with inelastic deformation of the host–inclusion pairs induced by the development of large differential stresses during experimental cooling. Therefore, inclusion strains are more reliable for inclusions trapped at lower temperature conditions in the α-quartz field where there is less inelastic deformation of the host–inclusion systems. On the other hand, entrapment isomekes of zircon inclusions entrapped in the β-quartz stability field plot along the α–β quartz phase boundary, suggesting that the inclusion strains were mechanically reset at the phase boundary during experimental cooling and decompression. Therefore, inclusions contained in soft host minerals can be used for elastic thermobarometry and inclusions contained in β-quartz may provide constraints on the P – T at which the host–inclusion system crossed the phase boundary during exhumation.

Opposing genetic patterns of range shifting temperate and tropical gastropods in an area undergoing tropicalisation - Karolina M. Zarzyczny; Michael E. Hellberg; Elena B. Lugli; Moira MacLean; David A. Paz‐García; Marc Rius; Ethan G. Ross; Erick X. Treviño Balandra; James Vanstone; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2024)
Aim The poleward range expansion of tropical species, and range contraction of temperate species (known as tropicalisation) has mainly been studied from an ecological perspective, with little research on its genetic consequences. Here, we used distributional and genetic data to document the consequences of tropicalisation in rocky shore gastropods and assess more broadly the future implications of tropicalisation on phylogeographic patterns. Location Nineteen sampling sites along >3000 km of the eastern Pacific rocky intertidal zone, from the tip of the Baja California Peninsula to southern California. Taxon Temperate gastropods: Lottia conus , L. strigatella , Fissurella volcano and Tegula gallina. Tropical gastropods: Fissurella rubropicta , Nerita funiculata and N. scabricosta. Methods We determine historical and modern distributions of tropical and temperate species by combining historical records with current field surveys. Using a section of the cytochrome oxidase subunit I gene, we utilised comparative phylogeography, analysis of molecular variance, F ST pairwise comparison, mismatch distributions of haplotype differences and neutrality tests to detect genetic signatures of tropicalisation and to better understand its consequences. Results We identified range contractions in two temperate species and range expansion in all three tropical species. We detected genetic signatures of range expansion in the tropical species through unimodal distributions of pairwise haplotype differences and strongly negative values for the Fu and Li D and F * statistics. We found population subdivision and phylogeographic breaks in three temperate species, although the geographic location of the breaks differed among species. Main Conclusions Genetic signatures and field surveys indicate recent range expansions in tropical species, supporting tropicalisation along the studied coastline. Conversely, we found phylogeographic breaks in temperate species, suggesting that tropicalisation may cause genetic erosion of evolutionary distinct lineages with range‐contraction. The different locations of the phylogeographic breaks among temperate species suggests that some barriers are species specific.

Worms and welfare: Behavioural and physiological changes associated with gastrointestinal nematode parasitism in lambs - Melissa N. Hempstead; Tania S. Waghorn; Michaela J. Gibson; Christian W. Sauermann; Alastair B. Ross; Vanessa M. Cave; Mhairi A. Sutherland; Nelly Marquetoux; Rina Hannaford; Rene A. Corner-Thomas; Ian A. Sutherland (Veterinary Parasitology, 2023)

Symbiont-mediated tradeoffs between growth and heat tolerance are modulated by light and temperature in the coral Montipora capitata - Shayle B. Matsuda; Mariah L. Opalek; Raphael Ritson-Williams; Ruth D. Gates; Ross Cunning (Coral Reefs, 2023)

Food in my life: How Australian adolescents perceive and experience their foodscape - Kora Uhlmann; Helen Ross; Lisa Buckley; Brenda B. Lin (Appetite, 2023)

Filling the data gaps: Transferring models from data-rich to data-poor deep-sea areas to support spatial management - Amelia E.H. Bridges; David K.A. Barnes; James B. Bell; Rebecca E. Ross; Lizette Voges; Kerry L. Howell (Journal of Environmental Management, 2023)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Breastfeeding Experiences and Barriers Among Mothers with Perceived Insufficient Milk - T. Cousins; S. Ross; J. Demirci; S. Poston; B. Gibbs (Journal of the Academy of Nutrition and Dietetics, 2023)

Prototyping of a lateral flow assay based on monoclonal antibodies for detection of Bothrops venoms - Cecilie Knudsen; Jonas A. Jürgensen; Pelle D. Knudsen; Irina Oganesyan; Julian A. Harrison; Søren H. Dam; Aleksander M. Haack; Rasmus U.W. Friis; Lars Vitved; Selma B. Belfakir; Georgina M.S. Ross; Renato Zenobi; et al. (Analytica Chimica Acta, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Corrigendum to “Biomechanics of the mandible of Macaca mulatta during the power stroke of mastication: Loading, deformation, and strain regimes and the impact of food type” [Journal of Human Evolution 147 (2020) 102865] - Olga Panagiotopoulou; Jose Iriarte-Diaz; Hyab Mehari Abraha; Andrea B. Taylor; Simon Wilshin; Paul C. Dechow; Callum F. Ross (Journal of Human Evolution, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Declining concentrations of chlorinated paraffins in endangered St. Lawrence Estuary belugas (Delphinapterus leucas): Response to regulations or a change in diet? - Antoine É. Simond; Peter S. Ross; Jory Cabrol; Véronique Lesage; Stéphane Lair; Million B. Woudneh; Diwen Yang; Hui Peng; Katerina Colbourne; Tanya M. Brown (Science of The Total Environment, 2023)

At the interfaces of the hydrologic sciences: Connecting water, elements, ecosystems, and people through the major contributions of Dr. Emily Bernhardt - Ashley M. Helton; Jennifer L. Morse; Elizabeth B. Sudduth; Marcelo Ardón; Raven Bier; Kristofor A. Voss; Matthew R.V. Ross; Joanna R. Blaszczak; Jessica E. Brandt; Marie Simonin; Jennifer D. Rocca; Alice Carter; et al. (Journal of Hydrology, 2023)

Understanding communities’ perceptions, demographics and uses of wetlands in Vhembe Biosphere Reserve, South Africa - Mwazvita T. B. Dalu; Onica Mukhuwana; Ross N. Cuthbert; Thomas Marambanyika; Ashley W. Gunter; Florence M. Murungweni; Tatenda Dalu (Wetlands Ecology and Management, 2022)

Arctic char enter the marine environment before annual ice breakup in the high Arctic - Lars J. Hammer; Nigel E. Hussey; Marianne Marcoux; Harri Pettitt-Wade; Kevin Hedges; Ross Tallman; Nathan B. Furey (Environmental Biology of Fishes, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Alpinumisoflavone against cancer pro-angiogenic targets: In silico, In vitro, and In ovo evaluation - Honeymae C. Alos; Junie B. Billones; Agnes L. Castillo; Ross D. Vasquez (DARU Journal of Pharmaceutical Sciences, 2022)

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Inhaled nitric oxide does not improve maximal oxygen consumption in endurance trained and untrained healthy individuals - Andrew R. Brotto; Devin B. Phillips; Victoria L. Meah; Bryan A. Ross; Desi P. Fuhr; Rhys I. Beaudry; Sean van Diepen; Michael K. Stickland (European Journal of Applied Physiology, 2022)

TitaniQ revisited: expanded and improved Ti-in-quartz solubility model for thermobarometry - Zach R. Osborne; Jay B. Thomas; William O. Nachlas; Ross J. Angel; Christopher M. Hoff; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2022)

Insect gut bacteria: a promising tool for enhanced biogas production - Binoy Kumar Show; Sandipan Banerjee; Aishiki Banerjee; Richik GhoshThakur; Amit Kumar Hazra; Narayan Chandra Mandal; Andrew B. Ross; Srinivasan Balachandran; Shibani Chaudhury (Reviews in Environmental Science and Bio/Technology, 2022)

Temperature‐mediated acquisition of rare heterologous symbionts promotes survival of coral larvae under ocean warming - Shayle B. Matsuda; Leela J. Chakravarti; Ross Cunning; Ariana S. Huffmyer; Craig E. Nelson; Ruth D. Gates; Madeleine J. H. van Oppen (Global Change Biology, 2022)
Reef‐building corals form nutritional symbioses with endosymbiotic dinoflagellates (Symbiodiniaceae), a relationship that facilitates the ecological success of coral reefs. These symbionts are mostly acquired anew each generation from the environment during early life stages (“horizontal transmission”). Symbiodiniaceae species exhibit trait variation that directly impacts the health and performance of the coral host under ocean warming. Here, we test the capacity for larvae of a horizontally transmitting coral, Acropora tenuis , to establish symbioses with Symbiodiniaceae species in four genera that have varying thermal thresholds (the common symbiont genera, Cladocopium and Durusdinium , and the less common Fugacium and Gerakladium ). Over a 2‐week period in January 2018, a series of both no‐choice and four‐way choice experiments were conducted at three temperatures (27, 30, and 31°C). Symbiont acquisition success and cell proliferation were measured in individual larvae. Larvae successfully acquired and maintained symbionts of all four genera in no‐choice experiments, and >80% of larvae were infected with at least three genera when offered a four‐way choice. Unexpectedly, Gerakladium symbionts increased in dominance over time, and at high temperatures outcompeted Durusdinium , which is regarded as thermally tolerant. Although Fugacium displayed the highest thermal tolerance in culture and reached similar cell densities to the other three symbionts at 31°C, it remained a background symbiont in choice experiments, suggesting host preference for other symbiont species. Larval survivorship at 1 week was highest in larvae associated with Gerakladium and Fugacium symbionts at 27 and 30°C, however at 31°C, mortality was similar for all treatments. We hypothesize that symbionts that are currently rare in corals (e.g., Gerakladium ) may become more common and widespread in early life stages under climate warming. Uptake of such symbionts may function as a survival strategy in the wild, and has implications for reef restoration practices that use sexually produced coral stock.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Long-term monitoring of Vermont’s forest soils: early trends and efforts to address innate variability - Donald S. Ross; Scott W. Bailey; Thomas R. Villars; Angelica Quintana; Sandy Wilmot; James B. Shanley; Joshua M. Halman; James A. Duncan; Jennifer A. Bower (Environmental Monitoring and Assessment, 2021)

Patterns of Consumption Across a Caribbean Seascape: Roles of Habitat and Consumer Species Composition Through Time - Carmen J. Ritter; Leah M. Harper; Jonathan S. Lefcheck; Valerie J. Paul; Ross Whippo; Scott Jones; Matthew B. Ogburn; J. Emmett Duffy (Frontiers in Marine Science, 2021)
Herbivores, omnivores, and predators transfer energy and structure the communities of many coastal marine ecosystems, and the intensity with which they consume prey and contribute to ecosystem functioning varies substantially among habitats over short time periods. Whether generalities across habitats might emerge for longer time series and using standard methods remains largely untested. Here, we deployed standardized assays of consumption using dried squid (“squidpops”) and five common macrophytes (“weedpops”) to quantify consumption across coral fore reef and patch reefs, mangroves, seagrass meadows, and bare sand from 2015 to 2019 around Carrie Bow Cay, Belize. We also used video in 2017 to identify the species responsible for consumption. We found that both squid- and weedpop consumption were consistently highest on patch and fore reef habitats, moderate in mangroves, and lowest in seagrass and sand across all years of the survey. Videos showed that the majority of consumption on the reefs in 2017 could be attributed to < 5 fish species, and the identity of the dominant consumers differed among habitats. This study validates a key but implicit assumption in marine ecology that relative patterns in consumption across habitats are consistent through space and time in tropical nearshore environments, and reveals that high consumption rates may be the consequence of one or few species in each location.

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Overwintering and migration behaviour of post‐spawned Atlantic salmon Salmo salar in a large hydropower‐regulated river and reservoir - Amanda B. Babin; Mouhamed Ndong; Katy Haralampides; Stephan Peake; Ross Jones; R. Allen Curry; Tommi Linnansaari (Journal of Fish Biology, 2021)
Tracking 47 post‐spawned adult Atlantic salmon Salmo salar L. in a hydropower‐regulated river through autumn, winter and spring revealed that winter survival was 56% and 75% in two study years, respectively, with higher mortality of males than females (50% vs . 33% and 100% vs . 13%, respectively). Some kelts ( n = 7) displayed nondirected movements that were interpreted as a reconditioning period for an average of 9–17 days prior to directed downstream movements indicating the initiation of migration. Survival after the initiation of migration in spring was 83% and 94% to the hydropower dam in the first and second study years, and decreased to 60 and 63%, respectively, after dam passage. There were no further losses in the downriver reach in the second year, with the first year having a cumulative survival estimate of 53% to the river mouth. Kelts approached the dam when the spillway gates were available as a passage option most of the time (64%–75%), but some kelts arrived at the dam or had not yet passed when spillways were closed ( n = 6) and the only remaining passage option was restricted to the turbines. However, all but one kelt that must have passed via turbine were successful in reaching the river mouth. Migratory delay presumably due to searching behaviour caused by low water flow was estimated at approximately 6 days as migration rates were significantly slower in the reservoir (median ± s.e. 8.5 ± 2.5 km day −1 ) than up‐ (29.7 ± 5.0 km day −1 ) or downriver (22.1 ± 3.1 km day −1 ). The proportion of time (median 30%) that kelts spent swimming upstream (searching behaviour) in the reservoir was a significant variable for migration success.

Optimizing hatchery practices for genetic improvement of marine bivalves - Jennifer C. Nascimento‐Schulze; Tim P. Bean; Ross D. Houston; Eduarda M. Santos; Matthew B. Sanders; Ceri Lewis; Robert P. Ellis (Reviews in Aquaculture, 2021)
Aquaculture currently accounts for approximately half of all seafood produced and is the fastest growing farmed food sector globally. Marine bivalve aquaculture, the farming of oysters, mussels and clams, represents a highly sustainable component of this industry and has major potential for global expansion via increased efficiency, and numbers of, production systems. Artificial spat propagation (i.e. settled juveniles) in hatcheries and selective breeding have the potential to offer rapid and widespread gains for molluscan aquaculture industry. However, bivalves have unique life‐histories, genetic and genomic characteristics, which present significant challenges to achieving such genetic improvement. Selection pressures experienced by bivalve larvae and spat in the wild contribute to drive population structure and animal fitness. Similarly, domestication selection is likely to act on hatchery‐produced spat, the full implications of which have not been fully explored. In this review, we outline the key features of these taxa and production practices applied in bivalve aquaculture, which have the potential to affect the genetic and phenotypic variability of hatchery‐propagated stock. Alongside, we compare artificial and natural processes experienced by bivalves to investigate the possible consequences of hatchery propagation on stock production. In addition, we identify key areas of investigation that need to be prioritized to continue to the advancement of bivalve genetic improvement via selective breeding. The growing accessibility of next‐generation sequencing technology and high‐powered computational capabilities facilitate the implementation of novel genomic tools in breeding programmes of aquatic species. These emerging techniques represent an exciting opportunity for sustainably expanding the bivalve aquaculture sector.

2,4-Dichlorophenoxyacetic acid degradation in methanogenic mixed cultures obtained from Brazilian Amazonian soil samples - Gunther Brucha; Andrea Aldas-Vargas; Zacchariah Ross; Peng Peng; Siavash Atashgahi; Hauke Smidt; Alette Langenhoff; Nora B. Sutton (Biodegradation, 2021)
2,4-Dichlorophenoxyacetic acid (2,4-D) is the third most applied pesticide in Brazil to control broadleaf weeds in crop cultivation and pastures. Due to 2,4-D’s high mobility and long half-life under anoxic conditions, this herbicide has high probability for groundwater contamination. Bioremediation is an attractive solution for 2,4-D contaminated anoxic environments, but there is limited understanding of anaerobic 2,4-D biodegradation. In this study, methanogenic enrichment cultures were obtained from Amazonian top soil (0—40 cm) and deep soil (50 -80 cm below ground) that biotransform 2,4-D (5 µM) to 4-chlorophenol and phenol. When these cultures were transferred (10% v/v) to fresh medium containing 40 µM or 160 µM 2,4-D, the rate of 2,4-D degradation decreased, and biotransformation did not proceed beyond 4-chlorophenol and 2,4-dichlorophenol in the top and deep soil cultures, respectively. 16S rRNA gene sequencing and qPCR of a selection of microbes revealed no significant enrichment of known organohalide-respiring bacteria. Furthermore, a member of the genus Cryptanaerobacter was identified as possibly responsible for phenol conversion to benzoate in the top soil inoculated culture. Overall, these results demonstrate the effect of 2,4-D concentration on biodegradation and microbial community composition, which are both important factors when developing pesticide bioremediation technologies.

Tropicalization of temperate ecosystems in North America: The northward range expansion of tropical organisms in response to warming winter temperatures - Michael J. Osland; Philip W. Stevens; Margaret M. Lamont; Richard C. Brusca; Kristen M. Hart; J. Hardin Waddle; Catherine A. Langtimm; Caroline M. Williams; Barry D. Keim; Adam J. Terando; Eric A. Reyier; Katie E. Marshall; et al. (Global Change Biology, 2021)
Tropicalization is a term used to describe the transformation of temperate ecosystems by poleward‐moving tropical organisms in response to warming temperatures. In North America, decreases in the frequency and intensity of extreme winter cold events are expected to allow the poleward range expansion of many cold‐sensitive tropical organisms, sometimes at the expense of temperate organisms. Although ecologists have long noted the critical ecological role of winter cold temperature extremes in tropical–temperate transition zones, the ecological effects of extreme cold events have been understudied, and the influence of warming winter temperatures has too often been left out of climate change vulnerability assessments. Here, we examine the influence of extreme cold events on the northward range limits of a diverse group of tropical organisms, including terrestrial plants, coastal wetland plants, coastal fishes, sea turtles, terrestrial reptiles, amphibians, manatees, and insects. For these organisms, extreme cold events can lead to major physiological damage or landscape‐scale mass mortality. Conversely, the absence of extreme cold events can foster population growth, range expansion, and ecological regime shifts. We discuss the effects of warming winters on species and ecosystems in tropical–temperate transition zones. In the 21st century, climate change‐induced decreases in the frequency and intensity of extreme cold events are expected to facilitate the poleward range expansion of many tropical species. Our review highlights critical knowledge gaps for advancing understanding of the ecological implications of the tropicalization of temperate ecosystems in North America.

Four decades of reef observations illuminate deep‐water grouper hotspots - Avery B. Paxton; Stacey L. Harter; Steve W. Ross; Christina M. Schobernd; Brendan J. Runde; Paul J. Rudershausen; Katrina H. Johnson; Kyle W. Shertzer; Nathan M. Bacheler; Jeffrey A. Buckel; G. Todd Kellison; J. Christopher Taylor (Fish and Fisheries, 2021)
Fish often aggregate to spawn, feed, rest, or avoid predation. Direct observations of very high counts of large‐bodied grouper on deep shipwrecks, however, do not fit into typical descriptions of spawning‐, resource‐, or predation‐driven aggregations. To investigate whether these observations are rare or part of an underlying pattern, we synthesized four decades (1979–2019) of direct observations of groupers on deep‐water (50–300 m) habitats along the southeastern United States (Cape Hatteras, NC to Cape Canaveral, FL). The direct observations, which included 439 remotely operated vehicle transects, 235 human‐occupied vehicle transects, and 881 hook‐and‐line drops, revealed six hotspots of deep‐water groupers on three shipwrecks, two artificial reefs, and one boulder field. Grouper counts at these hotspots (0.10–5.40 grouper per linear m surveyed) exceeded counts of grouper outside of hotspots (

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Electro-Thermal Therapy Algorithms and Active Internal Electrode Cooling Reduce Thermal Injury in High Frequency Pulsed Electric Field Cancer Therapies - Michael B. Sano; Christopher C. Fesmire; Ross A. Petrella (Annals of Biomedical Engineering, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

The legacy of pasture drill rows on soil chemical characteristics and subsequent wheat production - Richard C. Hayes; Guangdi D. Li; Richard P. Rawnsley; Keith G. Pembleton; Ross Corkrey; Mark B. Peoples (Plant and Soil, 2020)

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Temperature Dependence of High Frequency Irreversible Electroporation Evaluated in a 3D Tumor Model - Christopher C. Fesmire; Ross A. Petrella; Callie A. Fogle; David A. Gerber; Lei Xing; Michael B. Sano (Annals of Biomedical Engineering, 2020)

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Citizen science data accurately predicts expert-derived species richness at a continental scale when sampling thresholds are met - Corey T. Callaghan; J. Dale Roberts; Alistair G. B. Poore; Ross A. Alford; Hal Cogger; Jodi J. L. Rowley (Biodiversity and Conservation, 2020)

Refining the ice flow chronology and subglacial dynamics across the migrating Labrador Divide of the Laurentide Ice Sheet with age constraints on deglaciation - Jessey M. Rice; Martin Ross; Roger C. Paulen; Samuel E. Kelley; Jason P. Briner; Christina M. Neudorf; Olav B. Lian (Journal of Quaternary Science, 2019)
The Laurentide Ice Sheet was characterized by a dynamic polythermal base. However, important data and knowledge gaps have led to contrasting reconstructions in areas such as the Labrador Ice Divide. In this study, detailed fieldwork was conducted at the southeastern edge of a major landform boundary to resolve the relative ice flow chronology and constrain the evolution of the subglacial dynamics, including the migration and collapse of the Labrador Ice Divide. Surficial mapping and analysis of 94 outcrop‐scale ice flow indicators were used to develop a relative ice flow chronology. 10 Be exposure ages were used with optical ages to confine the timing of deglaciation within the study area. Four phases of ice flow were identified. Flow 1 was a northeasterly ice flow preserved under non‐erosive subglacial conditions associated with the development of an ice divide. Flow 2 was a northwest ice flow, which we correlate to the Ungava Bay Ice Stream and led to a westward migration of the ice divide, preserving Flow 2 features and resulting in Flow 3's eastward‐trending indicators. Flow 4 is limited to sparse fine striations within and around the regional uplands. The new optical ages and 10 Be exposure ages add to the regional geochronology dataset, which further constrains the timing of ice margin retreat in the area to around 8.0 ka. Copyright © 2019 The Authors. Journal of Quaternary Science Published by John Wiley & Sons Ltd.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Using Time-Resolved Fluorescence Anisotropy of di-4-ANEPPDHQ and F2N12S to Analyze Lipid Packing Dynamics in Model Systems - Harmen B. B. Steele; Matthew J. Sydor; Donald S. Anderson; Andrij Holian; J. B. Alexander Ross (Journal of Fluorescence, 2019)

The heat penalty of walkable neighbourhoods - Grace A. O’Brien; Nancy A. Ross; Ian B. Strachan (International Journal of Biometeorology, 2019)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Abiotic reduction of Cr(VI) by humic acids derived from peat and lignite: kinetics and removal mechanism - Suha T. Aldmour; Ian T. Burke; Andrew W. Bray; Daniel L. Baker; Andrew B. Ross; Fiona L. Gill; Giannantonio Cibin; Michael E. Ries; Douglas I. Stewart (Environmental Science and Pollution Research, 2019)

Similar neurocognitive outcomes after 48 weeks in HIV-1-infected participants randomized to continue tenofovir/emtricitabine + atazanavir/ritonavir or simplify to abacavir/lamivudine + atazanavir - Kevin Robertson; Paul Maruff; Lisa L. Ross; David Wohl; Catherine B Small; Howard Edelstein; Mark S. Shaefer (Journal of NeuroVirology, 2019)

Chemical and biological studies on Bridelia ferruginea grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Samir A. Ross (Natural Product Research, 2019)

Phytochemical study of Piliostigma thonningii, a medicinal plant grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Abayomi Orishadipe; Fazila Zulfiqar; Mohamed A. Ibrahim; Samir A Ross (Medicinal Chemistry Research, 2018)

Correction to: Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

Novel disturbance interactions between fire and an emerging disease impact survival and growth of resprouting trees - Allison B. Simler; Margaret R. Metz; Kerri M. Frangioso; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2018)
Human‐altered ecological disturbances may challenge system resilience and disrupt biological legacies maintaining ecosystem recovery. Yet, the extent to which novel regimes challenge these legacies varies. This may be partially explained by differences in the vulnerability of life history strategies to disturbance characteristics. In the fire‐prone, resprouter‐dominated coast redwood forests of California, the introduced disease sudden oak death (SOD) alters fuel profiles, fire behavior, and aboveground tree mortality; however, this system is dominated by resprouting trees that are well‐adapted to aboveground damage, and belowground survival of individuals may represent the principal biological legacy connecting pre‐ and post‐fire communities. Much of the research exploring altered disturbances and forest recovery has focused on legacies determined by seed dispersal and aboveground survival of adults. In this work, we use pre‐ and post‐fire data from a long‐term monitoring network to assess the impacts of novel disturbance interactions between wildfire and SOD on the belowground survival and vegetative reproduction of resprouters. We found that increasing accumulation of coarse woody surface fuels from SOD‐killed hosts decreased the likelihood of belowground survival for resprouting tanoak trees, but not for redwoods. Tanoaks' belowground survival was negatively related to substrate burn severity, which increased with the volume of surface fuels from hosts, suggesting heat damage as a possible mechanism influencing altered patterns of resprouter mortality. These impacts increased with decreasing tree size. By contrast, redwood and tanoak trees that survived both disturbances resprouted more vigorously, regardless of post‐fire infection by P. ramorum , and generated similar recruitment at the stand level. Our results demonstrate that disease–fire interactions can narrow recruitment filters for resprouters, which could impact long‐term population and demographic structure; yet, compounded disturbance may also reduce stand density and disease pressure, allowing competitive release of survivors. Resprouters displayed vulnerabilities to altered disturbance, but our research suggests that legacies maintained by resprouting may be more resilient to certain compounded disturbances, compared to seed‐obligate species, because of high rates of individual survival under increasingly severe events. These trends have important implications for conservation of declining tree species in SOD‐impacted forests, as well as predictions of human impacts in other disturbance‐prone systems where resprouters are present.

Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

Minimizing opportunity costs to aquatic connectivity restoration while controlling an invasive species - Austin W. Milt; Matthew W. Diebel; Patrick J. Doran; Michael C. Ferris; Matthew Herbert; Mary L. Khoury; Allison T. Moody; Thomas M. Neeson; Jared Ross; Ted Treska; Jesse R. O'Hanley; Lisa Walter; et al. (Conservation Biology, 2018)
Controlling invasive species is critical for conservation but can have unintended consequences for native species and divert resources away from other efforts. This dilemma occurs on a grand scale in the North American Great Lakes, where dams and culverts block tributary access to habitat of desirable fish species and are a lynchpin of long‐standing efforts to limit ecological damage inflicted by the invasive, parasitic sea lamprey ( Petromyzon marinus ). Habitat restoration and sea‐lamprey control create conflicting goals for managing aging infrastructure. We used optimization to minimize opportunity costs of habitat gains for 37 desirable migratory fishes that arose from restricting sea lamprey access (0–25% increase) when selecting barriers for removal under a limited budget (US$1–105 million). Imposing limits on sea lamprey habitat reduced gains in tributary access for desirable species by 15–50% relative to an unconstrained scenario. Additional investment to offset the effect of limiting sea‐lamprey access resulted in high opportunity costs for 30 of 37 species (e.g., an additional US$20–80 million for lake sturgeon [ Acipenser fulvescens ]) and often required ≥5% increase in sea‐lamprey access to identify barrier‐removal solutions adhering to the budget and limiting access. Narrowly distributed species exhibited the highest opportunity costs but benefited more at less cost when small increases in sea‐lamprey access were allowed. Our results illustrate the value of optimization in limiting opportunity costs when balancing invasion control against restoration benefits for diverse desirable species. Such trade‐off analyses are essential to the restoration of connectivity within fragmented rivers without unleashing invaders.

White matter abnormalities in mild traumatic brain injury with and without post-traumatic stress disorder: a subject-specific diffusion tensor imaging study - Christian Lepage; Amicie de Pierrefeu; Inga K. Koerte; Michael J. Coleman; Ofer Pasternak; Gerald Grant; Christine E. Marx; Rajendra A. Morey; Laura A. Flashman; Mark S. George; Thomas W. McAllister; Norberto Andaluz; et al. (Brain Imaging and Behavior, 2018)

The biology, ecology and history of toheroa ( Paphies ventricosa ): a review of scientific, local and customary knowledge - P. M. Ross; M. P. Beentjes; J. Cope; W. P. de Lange; B. G. McFadgen; P. Redfearn; B. Searle; M. Skerrett; H. Smith; S. Smith; J. Te Tuhi; J. Tamihana; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
Toheroa ( Paphies ventricosa ) were formerly abundant on west and south‐facing New Zealand surf beaches. Harvesting of this surf clam was intense during the early to mid‐1900s, and populations declined to levels where harvesting was no longer viable. Despite having now been protected for 35–45 years, toheroa have failed to recover. This paper reviews the history of human interactions with toheroa and our understanding of their ecology, with a view to identifying knowledge requirements for management and restoration. Historical and legal documents pertaining to the use of marine resources are reviewed and scientific understanding compared with customary and local knowledge. We consider the factors that may be preventing toheroa recovery and make recommendations for research into life history, habitat requirements and the ecological consequences of changing land use. Management options are suggested to address the effects of vehicle use on beaches, poaching and the failings of the customary harvest system.

Multi-site harmonization of diffusion MRI data in a registration framework - Hengameh Mirzaalian; Lipeng Ning; Peter Savadjiev; Ofer Pasternak; Sylvain Bouix; Oleg Michailovich; Sarina Karmacharya; Gerald Grant; Christine E. Marx; Rajendra A. Morey; Laura A. Flashman; Mark S. George; et al. (Brain Imaging and Behavior, 2018)

Sensory Evaluation of Eleven Baked Russet-type Potato Varieties and Clones - Rulon R. Spear; Zach J. Holden; C. F. Ross; B. J. Weddell; Mark J. Pavek (American Journal of Potato Research, 2018)

Role of cytochrome P450 2B sequence variation and gene copy number in facilitating dietary specialization in mammalian herbivores - Smiljka Kitanovic; Teri J. Orr; Daniel Spalink; Granger B. Cocke; Katharina Schramm; P. Ross Wilderman; James R. Halpert; M. Denise Dearing (Molecular Ecology, 2018)
Theory postulates that dietary specialization in mammalian herbivores is enabled by a specialized set of liver enzymes that process the high concentrations of similar plant secondary metabolites (PSMs) in the diets of specialists. To investigate whether qualitative and quantitative differences in detoxification mechanisms distinguish dietary specialists from generalists, we compared the sequence diversity and gene copy number of detoxification enzymes in two woodrat species: a generalist, the white‐throated woodrat ( Neotoma albigula ) and a juniper specialist, Stephens’ woodrat ( N. stephensi ). We focused on enzymes in the cytochrome P450 subfamily 2B (CYP2B), because previous research suggests this subfamily plays a key role in the processing of PSMs. For both woodrat species, we obtained and sequenced CYP2B cDNA, generated CYP2B phylogenies, estimated CYP2B gene copy number and created a homology model of the active site. We found that the specialist possessed on average ~5 more CYP2B gene copies than the generalist, but the specialist's CYP2B sequences were less diverse. Phylogenetic analysis of putative CYP2B homologs resolved woodrat species as reciprocally monophyletic and suggested evolutionary convergence of distinct homologs on similar key amino acid residues in both species. Homology modelling of the CYP2B enzyme suggests that interspecific differences in substrate preference and function likely result from amino acid differences in the enzyme active site. The characteristics of CYP2B in the specialist, that is greater gene copy number coupled with less sequence variation, are consistent with specialization to a narrow range of dietary toxins.

New tetranorlabdanoic acid from aerial parts of Salvia aethiopis - Radhakrishnan Srivedavyasasri; Miriah B. White; Tatyana S. Kustova; Nadezhda G. Gemejiyeva; Charles L. Cantrell; Samir A. Ross (Natural Product Research, 2018)

First detection of gas bubble disease and Rickettsia ‐like organisms in Paphies ventricosa , a New Zealand surf clam - P M Ross; A Pande; J B Jones; J Cope; G Flowers (Journal of Fish Diseases, 2018)

Transcriptomic profiling of adaptive responses to ocean acidification - Priscila Goncalves; David B. Jones; Emma L. Thompson; Laura M. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2017)
Some populations of marine organisms appear to have inherent tolerance or the capacity for acclimation to stressful environmental conditions, including those associated with climate change. Sydney rock oysters from the B2 breeding line exhibit resilience to ocean acidification ( OA ) at the physiological level. To understand the molecular basis of this physiological resilience, we analysed the gill transcriptome of B2 oysters that had been exposed to near‐future projected ocean pH over two consecutive generations. Our results suggest that the distinctive performance of B2 oysters in the face of OA is mediated by the selective expression of genes involved in multiple cellular processes. Subsequent high‐throughput qPCR revealed that some of these transcriptional changes are exclusive to B2 oysters and so may be associated with their resilience to OA . The intracellular processes mediated by the differentially abundant genes primarily involve control of the cell cycle and maintenance of cellular homeostasis. These changes may enable B2 oysters to prevent apoptosis resulting from oxidative damage or to alleviate the effects of apoptosis through regulation of the cell cycle. Comparative analysis of the OA conditioning effects across sequential generations supported the contention that B2 and wild‐type oysters have different trajectories of changing gene expression and responding to OA . Our findings reveal the broad set of molecular processes underlying transgenerational conditioning and potential resilience to OA in a marine calcifier. Identifying the mechanisms of stress resilience can uncover the intracellular basis for these organisms to survive and thrive in a rapidly changing ocean.

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

Distribution and socio-ecological impacts of the invasive alien cactus Opuntia stricta in eastern Africa - Ross T. Shackleton; Arne B. R. Witt; Francis M. Piroris; Brian W. van Wilgen (Biological Invasions, 2017)

Identification of Spilled Oil from the MV Marathassa (Vancouver, Canada 2015) Using Alkyl PAH Isomer Ratios - Carmen Morales-Caselles; Mark B. Yunker; Peter S. Ross (Archives of Environmental Contamination and Toxicology, 2017)

Factors influencing the post-exercise hepcidin-25 response in elite athletes - Peter Peeling; Alannah K. A. McKay; David B. Pyne; Kym J. Guelfi; Rachel H. McCormick; Coby M. Laarakkers; Dorine W. Swinkels; Laura A. Garvican-Lewis; Megan L. R. Ross; Avish P. Sharma; Jill J. Leckey; Louise M. Burke (European Journal of Applied Physiology, 2017)

Whole grain in manufactured foods: Current use, challenges and the way forward - Christelle Schaffer-Lequart; Undine Lehmann; Alastair B. Ross; Olivier Roger; Alison L. Eldridge; Edwin Ananta; Marie-France Bietry; Luis R. King; Alice V. Moroni; Sathaporn Srichuwong; Anne-Sophie Wavreille; Robert Redgwell; et al. (Critical Reviews in Food Science and Nutrition, 2017)

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Approaches to Landscape Scale Inference and Study Design - Ross B. Cunningham; David B. Lindenmayer (Current Landscape Ecology Reports, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Stable isotope paleohydrology and chemostratigraphy of the Albian Wayan Formation from the wedge-top depozone, North American Western Interior Basin - Jeffrey B. Ross; Greg A. Ludvigson; Andreas Möller; Luis A. Gonzalez; J. D. Walker (Science China Earth Sciences, 2017)

Connecting the trophic dots: responses of an aquatic bird species to variable abundance of macroinvertebrates in northern boreal wetlands - K. E. B. Gurney; R. G. Clark; S. M. Slattery; L. C. M. Ross (Hydrobiologia, 2017)

The association of medication use with clearance or persistence of oral HPV infection - Jennifer O. Lam; Elizabeth A. Sugar; Ross D. Cranston; Kathleen M. Weber; Robert D. Burk; Dorothy J. Wiley; Susheel Reddy; Joseph B. Margolick; Howard D. Strickler; Alicia Wentz; Lisa Jacobson; Christian L. Coles; et al. (Cancer Causes & Control, 2016)

Sheep grazing in the North Atlantic region: A long-term perspective on environmental sustainability - Louise C. Ross; Gunnar Austrheim; Leif-Jarle Asheim; Gunnar Bjarnason; Jon Feilberg; Anna Maria Fosaa; Alison J. Hester; Øystein Holand; Ingibjörg S. Jónsdóttir; Lis E. Mortensen; Atle Mysterud; Erla Olsen; et al. (Ambio, 2016)

Effects of the receiving assemblage and disturbance on the colonisation of an invasive species - Ana B. Bugnot; Ross A. Coleman; Will F. Figueira; Ezequiel M. Marzinelli (Marine Biology, 2016)

Enriched Groundwater Seeps in Two Vermont Headwater Catchments are Hotspots of Nitrate Turnover - Amninder J. Kaur; Donald S. Ross; James B. Shanley; Anna R. Yatzor (Wetlands, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

The Effects of Experimentally Induced Low Back Pain on Spine Rotational Stiffness and Local Dynamic Stability - Gwyneth B. Ross; Matthew Mavor; Stephen H. M. Brown; Ryan B. Graham (Annals of Biomedical Engineering, 2015)

Community-level impacts of the invasive isopod Cirolana harfordi - Ana B. Bugnot; Ross A. Coleman; Will F. Figueira; Ezequiel M. Marzinelli (Biological Invasions, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

DSP4, a Selective Neurotoxin for the Locus Coeruleus Noradrenergic System. A Review of Its Mode of Action - Svante B. Ross; Carina Stenfors (Neurotoxicity Research, 2015)

Genetic basis of interindividual susceptibility to cancer cachexia: selection of potential candidate gene polymorphisms for association studies - N. JOHNS; B. H. TAN; M. MACMILLAN; T. S. SOLHEIM; J. A. ROSS; V. E. BARACOS; S. DAMARAJU; K. C. H. FEARON (Journal of Genetics, 2014)

Geographic influences on fine-scale, hierarchical population structure in northern Canadian populations of anadromous Arctic Char (Salvelinus alpinus) - Les N. Harris; Jean-Sébastien Moore; Paul Galpern; Ross F. Tallman; Eric B. Taylor (Environmental Biology of Fishes, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Deep-bedded ultramafic diatremes in the Missouri River Breaks volcanic field, Montana, USA: 1 km of syn-eruptive subsidence - Séverine Delpit; Pierre-Simon Ross; B. Carter Hearn (Bulletin of Volcanology, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Groundwater resource potential of the Triassic Sandstones of the Southern Sydney Basin: an improved understanding - J. B. Ross (Australian Journal of Earth Sciences, 2014)

The Next Direction for Primatology? A Commentary on Setchell (2013) - Lydia M. Hopper; David B. Morgan; Stephen R. Ross (International Journal of Primatology, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Pauling bond strength, bond length and electron density distribution - G. V. Gibbs; N. L. Ross; D. F. Cox; K. M. Rosso; B. B. Iversen; M. A. Spackman (Physics and Chemistry of Minerals, 2014)

The allure and peril of hematopoietic stem cell transplantation: overcoming immune challenges to improve success - Robert G. Newman; Duncan B. Ross; Henry Barreras; Samantha Herretes; Eckhard R. Podack; Krishna V. Komanduri; Victor L. Perez; Robert B. Levy (Immunologic Research, 2013)

Rust disease of eucalypts, caused by P uccinia psidii , did not originate via host jump from guava in B razil - Rodrigo N. Graça; Amy L. Ross‐Davis; Ned B. Klopfenstein; Mee‐Sook Kim; Tobin L. Peever; Phil G. Cannon; Cristina P. Aun; Eduardo S. G. Mizubuti; Acelino C. Alfenas (Molecular Ecology, 2013)
The rust fungus, P uccinia psidii , is a devastating pathogen of introduced eucalypts ( E ucalyptus spp.) in Brazil where it was first observed in 1912. This pathogen is hypothesized to be endemic to S outh and C entral A merica and to have first infected eucalypts via a host jump from native guava ( P sidium guajava ). Ten microsatellite markers were used to genotype 148 P . psidii samples from eucalypts and guava plus five additional myrtaceous hosts across a wide geographic range of south‐eastern Brazil and Uruguay. Principal coordinates analysis, a B ayesian clustering analysis and a minimum‐spanning network revealed two major genetic clusters among the sampled isolates, one associated with guava and another associated with eucalypts and three additional hosts. M ultilocus genotypes infecting guava differed by multiple mutational steps at eight loci compared with those infecting eucalypts. Approximate B ayesian computation revealed that evolutionary scenarios involving a coalescence event between guava‐ and eucalypt‐associated pathogen populations within the past 1000 years are highly unlikely. None of the analyses supported the hypothesis that eucalypt‐infecting P . psidii in Brazil originated via host jump from guava following the introduction of eucalypts to Brazil approximately 185 years ago. The existence of host‐associated biotypes of P . psidii in Brazil indicates that this diversity must be considered when assessing the invasive threat posed by this pathogen to myrtaceous hosts worldwide.

Crustal architecture of the Capricorn Orogen, Western Australia and associated metallogeny - S. P. Johnson; A. M. Thorne; I. M. Tyler; R. J. Korsch; B. L. N. Kennett; H. N. Cutten; J. Goodwin; O. Blay; R. S. Blewett; A. Joly; M. C. Dentith; A. R. A. Aitken; et al. (Australian Journal of Earth Sciences, 2013)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Erratum to: Arthropod Predation by a Specialist Seed Predator, the Golden-backed Uacari (Cacajao melanocephalus ouakary, Pitheciidae) in Brazilian Amazonia - A. A. Barnett; B. Ronchi-Teles; T. Almeida; A. Deveny; V. Schiel-Baracuhy; W. Sousa Silva; W. Spironello; C. Ross; A. MacLarnon (International Journal of Primatology, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

The in vivo pharmacodynamics of the novel opioid receptor antagonist, TD-1211, in models of opioid-induced gastrointestinal and CNS activity - Scott R. Armstrong; Christina B. Campbell; Carrie L. Richardson; Ross G. Vickery; Pamela R. Tsuruda; Daniel D. Long; Sharath S. Hegde; David T. Beattie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

An overview approach to seismic awareness for a “quiescent” region - Alena Rein; Ross B. Corotis (Natural Hazards, 2013)

Arthropod Predation by a Specialist Seed Predator, the Golden-backed Uacari (Cacajao melanocephalus ouakary, Pitheciidae) in Brazilian Amazonia - A. A. Barnett; B. Ronchi-Teles; T. Almeida; A. Deveny; V. Schiel-Baracuhy; W. Souza-Silva; W. Spironello; C. Ross; A. MacLarnon (International Journal of Primatology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Contrasting fire responses to climate and management: insights from two Australian ecosystems - Karen J King; Geoffrey J Cary; Ross A Bradstock; Jonathan B Marsden‐Smedley (Global Change Biology, 2013)
This study explores effects of climate change and fuel management on unplanned fire activity in ecosystems representing contrasting extremes of the moisture availability spectrum (mesic and arid). Simulation modelling examined unplanned fire activity (fire incidence and area burned, and the area burned by large fires) for alternate climate scenarios and prescribed burning levels in: (i) a cool, moist temperate forest and wet moorland ecosystem in south‐west T asmania (mesic); and (ii) a spinifex and mulga ecosystem in central A ustralia (arid). Contemporary fire activity in these case study systems is limited, respectively, by fuel availability and fuel amount. For future climates, unplanned fire incidence and area burned increased in the mesic landscape, but decreased in the arid landscape in accordance with predictions based on these limiting factors. Area burned by large fires (greater than the 95th percentile of historical, unplanned fire size) increased with future climates in the mesic landscape. Simulated prescribed burning was more effective in reducing unplanned fire activity in the mesic landscape. However, the inhibitory effects of prescribed burning are predicted to be outweighed by climate change in the mesic landscape, whereas in the arid landscape prescribed burning reinforced a predicted decline in fire under climate change. The potentially contrasting direction of future changes to fire will have fundamentally different consequences for biodiversity in these contrasting ecosystems, and these will need to be accommodated through contrasting, innovative management solutions.

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Partial heat acclimation of athletes with spinal cord lesion - Paul C. Castle; B. Pasan Kularatne; John Brewer; Alexis R. Mauger; Ross A. Austen; James A. Tuttle; Nick Sculthorpe; Richard W. Mackenzie; Neil S. Maxwell; Anthony D. J. Webborn (European Journal of Applied Physiology, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Temporal variation in sex allocation in the mealybug Planococcus citri: adaptation, constraint, or both? - Laura Ross; Minke B. W. Langenhof; Ido Pen; David M. Shuker (Evolutionary Ecology, 2012)

Global patterns in the impact of marine herbivores on benthic primary producers - Alistair G. B. Poore; Alexandra H. Campbell; Ross A. Coleman; Graham J. Edgar; Veijo Jormalainen; Pamela L. Reynolds; Erik E. Sotka; John J. Stachowicz; Richard B. Taylor; Mathew A. Vanderklift; J. Emmett Duffy (Ecology Letters, 2012)
Despite the importance of consumers in structuring communities, and the widespread assumption that consumption is strongest at low latitudes, empirical tests for global scale patterns in the magnitude of consumer impacts are limited. In marine systems, the long tradition of experimentally excluding herbivores in their natural environments allows consumer impacts to be quantified on global scales using consistent methodology. We present a quantitative synthesis of 613 marine herbivore exclusion experiments to test the influence of consumer traits, producer traits and the environment on the strength of herbivore impacts on benthic producers. Across the globe, marine herbivores profoundly reduced producer abundance (by 68% on average), with strongest effects in rocky intertidal habitats and the weakest effects on habitats dominated by vascular plants. Unexpectedly, we found little or no influence of latitude or mean annual water temperature. Instead, herbivore impacts differed most consistently among producer taxonomic and morphological groups. Our results show that grazing impacts on plant abundance are better predicted by producer traits than by large‐scale variation in habitat or mean temperature, and that there is a previously unrecognised degree of phylogenetic conservatism in producer susceptibility to consumption.

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

NR4A Gene Expression Is Dynamically Regulated in the Ventral Tegmental Area Dopamine Neurons and Is Related to Expression of Dopamine Neurotransmission Genes - Jeffrey B. Eells; Josiah Wilcots; Scott Sisk; Shirley X. Guo-Ross (Journal of Molecular Neuroscience, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Habitat Use by Coastal Birds Inferred from Stable Carbon and Nitrogen Isotopes - Ross A. Brittain; Arndt Schimmelmann; David F. Parkhurst; Christopher B. Craft (Estuaries and Coasts, 2012)

Isolates of Fusarium graminearum collected 40–320 meters above ground level cause Fusarium head blight in wheat and produce trichothecene mycotoxins - D. G. Schmale; S. D. Ross; T. L. Fetters; P. Tallapragada; A. K. Wood-Jones; B. Dingus (Aerobiologia, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Effects of Sea-Level Rise and Anthropogenic Development on Priority Bird Species Habitats in Coastal Georgia, USA - Ross A. Brittain; Christopher B. Craft (Environmental Management, 2012)

Near-Surface Soil Carbon, Carbon/Nitrogen Ratio, and Tree Species Are Tightly Linked across Northeastern United States Watersheds - Donald S. Ross; Scott W. Bailey; Gregory B. Lawrence; James B. Shanley; Guinevere Fredriksen; Austin E. Jamison; Patricia A. Brousseau (Forest Science, 2011)
Forest soils hold large stores of carbon, with the highest concentrations in the surface horizons. In these horizons, both the total C mass and the C/N ratio may respond more rapidly to changes in tree species than lower horizons. We measured C and C/N ratios in the Oa or A horizon from 12 watersheds at 8 established forested research sites in the northeastern United States. The dominant tree species included Acer saccharum, Betula alleghaniensis, Fagus grandifolia, Picea rubens, and Tsuga canadensis. In 710 plots, both soil C (50–530 g kg−1) and the C/N ratio (11.6–45.3) had a wide range. In all but the Cone Pond watershed, both N concentration and the C/N ratio were strongly related to C content. For these 11 watersheds, the average C/N ratio = 9.5 + 0.030 × C g kg−1 (R2 = 0.97, P < 0.001). Ratios at Cone Pond were much higher than would be predicted from this equation and charcoal was found in numerous samples, suggesting a source of recalcitrant C. Averaged by watershed, C concentration was also significantly related to C pools. The carbon concentration of the horizons sampled was negatively related to A. saccharum + B. alleghaniensis dominance and positively related to conifer + F. grandifolia dominance. The strong relationships between C, C/N ratio, and species suggest predictable patterns in C accumulation in near-surface soils.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

MPP+-induced toxicity in the presence of dopamine is mediated by COX-2 through oxidative stress - Ya-Ching Hsieh; Ross B. Mounsey; Peter Teismann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Predicting Capacity Demand on Sanctuaries for African Chimpanzees (Pan troglodytes) - Lisa J. Faust; Doug Cress; Kay H. Farmer; Stephen R. Ross; Benjamin B. Beck (International Journal of Primatology, 2011)

The timing of sea ice formation and exposure to photosynthetically active radiation along the Western Antarctic Peninsula - Christian H. Fritsen; Jeramie C. Memmott; Robin M. Ross; Langdon B. Quetin; Maria Vernet; Eric D. Wirthlin (Polar Biology, 2011)

Toxicity of the Insecticide Terbufos, its Oxidation Metabolites, and the Herbicide Atrazine in Binary Mixtures to Ceriodaphnia cf dubia - Catherine B. Choung; Ross V. Hyne; Mark M. Stevens; Grant C. Hose (Archives of Environmental Contamination and Toxicology, 2011)

Abundance and site fidelity of Indo‐Pacific Humpback dolphins in the Great Sandy Strait, Queensland, Australia - Daniele De Biasi Cagnazzi; Peter L. Harrison; Graham J. B. Ross; Peter Lynch (Marine Mammal Science, 2011)
This study examined the population of Indo‐Pacific humpback dolphins, Sousa chinensis , inhabiting the Great Sandy Strait Marine Park, Queensland, Australia. A total of 106 dolphins were identified during 228 boat‐based surveys, completed between April 2004 and April 2007. Based on the distribution of resighted individuals and the pattern of associations, it was established that this population consists of two largely geographically distinct communities, referred to as the Northern Community (NC) and the Southern Community (SC). The only recorded interaction between the two groups was a single pod composed of one member of the NC and 11 dolphins from the SC. Abundance was estimated for the entire population and by geographical area using open population models. Estimates for the Great Sandy Strait indicate that about 150 dolphins ( N GSS = 148.4, SE = 8.3, 95% CI: 132.5–165.2) used this area during the study. The NC and SC total population sizes was estimated to be 76 ( N NGSS = 75.80, SE = 3.88, 95% CI = 71–86) and 75 ( N SGSS = 74.98, SE = 4.43, 95% CI: 66–83), respectively. Analysis of residence patterns indicates that a majority of the identified dolphins are long‐term residents.

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

A New Small-Bodied Species of Palaeonictis (Creodonta, Oxyaenidae) from the Paleocene-Eocene Thermal Maximum - Stephen G. B. Chester; Jonathan I. Bloch; Ross Secord; Doug M. Boyer (Journal of Mammalian Evolution, 2010)

Evidence that His349 acts as a pH-inducible switch to accelerate receptor-mediated iron release from the C-lobe of human transferrin - Ashley N. Steere; Shaina L. Byrne; N. Dennis Chasteen; Valerie C. Smith; Ross T. A. MacGillivray; Anne B. Mason (JBIC Journal of Biological Inorganic Chemistry, 2010)

A low concentration of atrazine does not influence the acute toxicity of the insecticide terbufos or its breakdown products to Chironomus tepperi - Catherine B. Choung; Ross V. Hyne; Mark M. Stevens; Grant C. Hose (Ecotoxicology, 2010)

Bioacoustic distances between the begging calls of brood parasites and their host species: a comparison of metrics and techniques - Louis Ranjard; Michael G. Anderson; Matt J. Rayner; Robert B. Payne; Ian McLean; James V. Briskie; Howard A. Ross; Dianne H. Brunton; Sarah M. N. Woolley; Mark E. Hauber (Behavioral Ecology and Sociobiology, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Regulation of the gibberellin pathway by auxin and DELLA proteins - Damian P. O’Neill; Sandra E. Davidson; Victoria C. Clarke; Yukika Yamauchi; Shinjiro Yamaguchi; Yuji Kamiya; James B. Reid; John J. Ross (Planta, 2010)

Oral and Pharyngeal Cancer Control and Early Detection - Sol Silverman; A. Ross Kerr; Joel B. Epstein (Journal of Cancer Education, 2010)

High-Resolution Remote Sensing of Upland Swamp Boundaries and Vegetation for Baseline Mapping and Monitoring - Ross B. Jenkins; Paul S. Frazier (Wetlands, 2010)

Natural History of Innate Host Defense Peptides - A. Linde; B. Wachter; O. P. Höner; L. Dib; C. Ross; A. R. Tamayo; F. Blecha; T. Melgarejo (Probiotics and Antimicrobial Proteins, 2009)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Isolation and Analysis of Bacteria with Antimicrobial Activities from the Marine Sponge Haliclona simulans Collected from Irish Waters - Jonathan Kennedy; Paul Baker; Clare Piper; Paul D. Cotter; Marcella Walsh; Marlies J. Mooij; Marie B. Bourke; Mary C. Rea; Paula M. O’Connor; R. Paul Ross; Colin Hill; Fergal O’Gara; et al. (Marine Biotechnology, 2009)

Liver fatty acid binding protein gene ablation enhances age-dependent weight gain in male mice - Gregory G. Martin; Barbara P. Atshaves; Avery L. McIntosh; H. Ross Payne; John T. Mackie; Ann B. Kier; Friedhelm Schroeder (Molecular and Cellular Biochemistry, 2009)

A Cross-Site Comparison of Factors Influencing Soil Nitrification Rates in Northeastern USA Forested Watersheds - Donald S. Ross; Beverley C. Wemple; Austin E. Jamison; Guinevere Fredriksen; James B. Shanley; Gregory B. Lawrence; Scott W. Bailey; John L. Campbell (Ecosystems, 2009)

Are Q ST – F ST comparisons for natural populations meaningful? - B. PUJOL; A. J. WILSON; R. I. C. ROSS; J. R. PANNELL (Molecular Ecology, 2008)
Comparisons between putatively neutral genetic differentiation amongst populations, F ST , and quantitative genetic variation, Q ST , are increasingly being used to test for natural selection. However, we find that approximately half of the comparisons that use only data from wild populations confound phenotypic and genetic variation. We urge the use of a clear distinction between narrow‐sense Q ST , which can be meaningfully compared with F ST , and phenotypic divergence measured between populations, P ST , which is inadequate for comparisons in the wild. We also point out that an unbiased estimate of Q ST can be found using the so‐called ‘animal model’ of quantitative genetics.

The effect of oxygen vacancies and aluminium substitution on the high-pressure properties of brownmillerite-structured Ca2Fe2−x Al x O5 - Carine B. Vanpeteghem; Ross J. Angel; Jing Zhao; Nancy L. Ross; Günther J. Redhammer; Friedrich Seifert (Physics and Chemistry of Minerals, 2008)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Antibiotic and Disinfectant Susceptibility Profiles of Vancomycin-Resistant Enterococcus faecium (VRE) Isolated from Community Wastewater in Texas - Ross C. Beier; Sara E. Duke; Richard L. Ziprin; Roger B. Harvey; Michael E. Hume; Toni L. Poole; H. Morgan Scott; Linda D. Highfield; Walid Q. Alali; Kathleen Andrews; Robin C. Anderson; David J. Nisbet (Bulletin of Environmental Contamination and Toxicology, 2008)

Population-based laboratory surveillance for Serratia species isolates in a large Canadian health region - K. B. Laupland; M. D. Parkins; D. B. Gregson; D. L. Church; T. Ross; J. D. D. Pitout (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Dietary patterns, Mediterranean diet, and endometrial cancer risk - Tapashi B. Dalvi; Alison J. Canchola; Pamela L. Horn-Ross (Cancer Causes & Control, 2007)

Potential cause of lethality of an allele implicated in social evolution in fire ants - Brittan L. Hallar; Michael J. B. Krieger; Kenneth G. Ross (Genetica, 2007)

Evidence that the mature leaves contribute auxin to the immature tissues of pea (Pisum sativum L.) - Corinne E. Jager; Gregory M. Symons; Naomi E. Glancy; James B. Reid; John J. Ross (Planta, 2007)

Potential protonation sites in the Al2SiO5 polymorphs based on polarized FTIR spectroscopy and properties of the electron density distribution - Jason B. Burt; Nancy L. Ross; G. V. Gibbs; George R. Rossman; Kevin M. Rosso (Physics and Chemistry of Minerals, 2007)

Microhomologies between T-DNA ends and target sites often occur in inverted orientation and may be responsible for the high frequency of T-DNA-associated inversions - Andreas E. Müller; Ross G. Atkinson; Robert B. Sandoval; Richard A. Jorgensen (Plant Cell Reports, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; Megan K. Laird; Blake B. Ross; David H. Vaughan; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; David H. Vaughan; Megan K. Laird; Blake B. Ross; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Genes flanking Xist in mouse and human are separated on the X chromosome in American marsupials - Alexander I. Shevchenko; Irina S. Zakharova; Eugeny A. Elisaphenko; Nicolay N. Kolesnikov; Siobhan Whitehead; Christine Bird; Mark Ross; Jennifer R. Weidman; Randy L. Jirtle; Tatiana V. Karamysheva; Nicolay B. Rubtsov; John L. VandeBerg; et al. (Chromosome Research, 2007)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Uncertainty in Calculations of Net Primary Production for Grasslands - W. K. Lauenroth; A. A. Wade; M. A. Williamson; B. E. Ross; S. Kumar; D. P. Cariveau (Ecosystems, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

ELF isosurface maps for the Al2SiO5 polymorphs - J. B. Burt; G. V. Gibbs; D. F. Cox; N. L. Ross (Physics and Chemistry of Minerals, 2006)

Population dynamics and growth of juveniles of the velvet swimming crab Necora puber (Decapoda: Portunidae) - James T. Lee; Ross A. Coleman; Malcolm B. Jones (Marine Biology, 2006)

A mapping of the electron localization function for earth materials - G. V. Gibbs; D. F. Cox; N. L. Ross; T. D. Crawford; J. B. Burt; K. M. Rosso (Physics and Chemistry of Minerals, 2005)

The brassinosteroid growth response in pea is not mediated by changes in gibberellin content - Corinne E. Jager; Gregory M. Symons; John J. Ross; Jennifer J. Smith; James B. Reid (Planta, 2005)

Impact of land use on the faecal microbial quality of hill‐country streams - A. Donnison; C. Ross; B. Thorrold (New Zealand Journal of Marine and Freshwater Research, 2004)
Faecal contamination of rural streams is of increasing concern in New Zealand. This study assessed hill‐country streams in the Whatawhata district that were impacted by pastoral farming, indigenous forest, or Pinus radiata forest; by measuring Escherichia coli bacteria at 14 sampling sites fortnightly for 2 years. E. coli concentrations were highest in streams flowing through grazed pasture. In both years there was a noticeable seasonal pattern in all streams irrespective of land use, with highest bacterial concentrations in summer and autumn and lowest in winter and early spring. There was no obvious correlation between E. coli concentration and rainfall or stream flow. In those streams impacted by a change in land use from pastoral to pines during the study, E. coli concentration fell rapidly and remained at levels lower than those in streams impacted by either indigenous or 7‐year pine forests. As E. coli was detected in all but two samples, the water in these streams is not suitable for human consumption. The pastoral streams consistently failed to meet stock drinking‐water guidelines (median concentration not greater than 100 E. coli 100 ml –1 ) and the forest streams failed to do so in summer. Twenty‐eight percent of pastoral samples, 25% of indigenous forest samples, 14% of 7‐year pine forest samples, and 5% in New Pines stream samples (after planting) had E. coli concentrations associated with a high level of risk for contact recreation (>500 E. coli 100 ml ‐1 ) and the high concentrations usually occurred in summer.

Effects of Chlorinated Solvents on Four Species of North American Amphibians - T. V. McDaniel; P. A. Martin; N. Ross; S. Brown; S. Lesage; B. D. Pauli (Archives of Environmental Contamination and Toxicology, 2004)

Detection of Lateral Gene Transfer Events in the Prokaryotic tRNA Synthetases by the Ratios of Evolutionary Distances Method - Kamyar Farahi; Gordon D. Pusch; Ross Overbeek; William B. Whitman (Journal of Molecular Evolution, 2004)

An auxin-inducible gene from loblolly pine ( Pinus taeda L.) is differentially expressed in mature and juvenile-phase shoots and encodes a putative transmembrane protein - Victor B. Busov; Eva Johannes; Ross W. Whetten; Ronald R. Sederoff; Steven L. Spiker; Carmen Lanz-Garcia; Barry Goldfarb (Planta, 2004)

Effects of long-term administration of the 5-hydroxytryptamine 1B receptor antagonist AR-A000002 to guinea pigs - Carina Stenfors; Charlotte Ahlgren; Hong Yu; Maria Wedn; Lars-Gunnar Larsson; Svante B. Ross (Psychopharmacology, 2004)

Changes in extracellular 5-HIAA concentrations as measured by in vivo microdialysis technique in relation to changes in 5-HT release - Carina Stenfors; Svante B. Ross (Psychopharmacology, 2004)

Pharmacology of a novel selective 5-hydroxytryptamine 1B receptor antagonist, AR-A000002 - Carina Stenfors; Teresa Hallerbck; Lars-Gunnar Larsson; Carin Wallsten; Svante B. Ross (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Biphasic Dissipation Kinetics for Dislodgeable Foliar Residues in Estimating Postapplication Occupational Exposures to Endosulfan - G. K. Whitmyre; J. H. Ross; C. Lunchick; B. Volger; S. Singer (Archives of Environmental Contamination and Toxicology, 2004)

VARIABILITY IN THE DIET OF HARBOR PORPOISES ( PHOCOENA PHOCOENA ) IN SCOTTISH WATERS 1992–2003 - M. B. Santos; G. J. Pierce; J. A. Learmonth; R. J. Reid; H. M. Ross; I. A. P. Patterson; D. G. Reid; D. Beare (Marine Mammal Science, 2004)
A bstract Interannual, seasonal, and regional variation in the diet of porpoises, Phocoena phocoena , in Scottish (UK) waters was studied using stomach contents of animals stranded between 1992 and 2003. Most samples came from the east coast (including many porpoises killed by bottlenose dolphins), with smaller numbers from the west coast and from Shetland. The most important prey types, in terms of contribution by number and mass, were whiting ( Merlangius merlangus ) and sand eels (Ammodytidae). Multivariate analysis confirmed the existence of regional, seasonal, and interannual variation in diet, as well as differences ( i. e. , biases) related to cause of death. These differences were further explored using univariate analyses. Sand eels were more important in the summer months (quarters 2 and 3) and on the east coast, whereas gadids were more important in winter and in the Shetland area. Some, but not all, observed trends in the numerical importance and size of prey taken were consistent with trends in abundance and size of fish taken during research trawl surveys. There was some evidence that porpoises Clupea harengus and sprat Sprattus sprattus ) formed a relatively small proportion of the diet, but their importance varied from year to year. Although possible methodological biases prevent firm conclusions, it appears that the importance of clupeids in porpoise diet may have decreased since the 1960s, mirroring the decline in North Sea herring abundance. The recovery of the North Sea herring stock in recent years is not as yet reflected in porpoise diet.

Ecological genetics of the barnacle, Hexaminius foliorum , within mangrove forests near Sydney, Australia - S. C. Claus; P. M. Ross; B. J. Richardson (Marine Biology, 2003)

Growth of larval krill, Euphausia superba , in fall and winter west of the Antarctic Peninsula - L. B. Quetin; R. M. Ross; T. K. Frazer; M. O. Amsler; C. Wyatt-Evens; S. A. Oakes (Marine Biology, 2003)

Krill ( Euphausia superba ) recruitment indices from the western Antarctic Peninsula: are they representative of larger regions? - V. Siegel; R. M. Ross; L. B. Quetin (Polar Biology, 2003)

Interactions Between Signals in Plant Development - James B. Reid; John J. Ross (Journal of Plant Growth Regulation, 2003)

Environmental control of fine root dynamics in a northern hardwood forest - GERALDINE L. TIERNEY; TIMOTHY J. FAHEY; PETER M. GROFFMAN; JANET P. HARDY; ROSS D. FITZHUGH; CHARLES T. DRISCOLL; JOSEPH B. YAVITT (Global Change Biology, 2003)
Understanding how exogenous and endogenous factors control the distribution, production and mortality of fine roots is fundamental to assessing the implications of global change, yet our knowledge of control over fine root dynamics remains rudimentary. To improve understanding of these processes, the present study developed regression relationships between environmental variables and fine root dynamics within a northern hardwood forest in New Hampshire, USA, which was experimentally manipulated with a snow removal treatment. Fine roots (

A Novel in-Vitro Technique for Studying Percutaneous Permeation with a Membrane-Coated Fiber and Gas Chromatography/Mass Spectrometry: Part I. Performances of the Technique and Determination of the Permeation Rates and Partition Coefficients of Chemical Mixtures - Xin-Rui Xia; Ronald E. Baynes; Nancy A. Monteiro-Riviere; Ross B. Leidy; Damian Shea; Jim E. Riviere (Pharmaceutical Research, 2003)

Development and Validation of a Herring Gull Embryo Toxicokinetic Model for PCBs - Ken G. Drouillard; Ross J. Norstrom; Glen A. Fox; Andy Gilman; David B. Peakall (Ecotoxicology, 2003)

Use of the firefly luciferase gene in a barley ( Hordeum vulgare ) transformation system - W. Harwood; S. Ross; S. Bulley; S. Travella; B. Busch; J. Harden; J. Snape (Plant Cell Reports, 2002)

Mechanisms of competition: thermal inhibition of tree seedling growth by grass - Marilyn C. Ball; J. Egerton; Jason L. Lutze; Vincent P. Gutschick; Ross B. Cunningham (Oecologia, 2002)

Genetic, physical, and comparative map of the subtelomeric region of mouse Chromosome 4 - Xia Li; Alexander A. Bachmanov; Shanru Li; Zhenyu Chen; Michael G. Tordoff; Gary K. Beauchamp; Pieter J. de Jong; Chenyan Wu; Lianchun Chen; David B. West; David A. Ross; Jeffery D. Ohmen; et al. (Mammalian Genome, 2002)

A Simplified Liquid-Solid Extraction Technique for the Analyses of Pesticide Residues in Soil Samples - Xin-Rui Xia; Ross B. Leidy (Environmental Monitoring and Assessment, 2002)

Auxin-Gibberellin Interactions and Their Role in Plant Growth - John J. Ross; Damian P. O'Neill; Carla M. Wolbang; Gregory M. Symons; James B. Reid (Journal of Plant Growth Regulation, 2001)

Feed-Forward Regulation of Gibberellin Deactivation in Pea - Robert C. Elliott; John J. Ross; Jennifer J. Smith; Diane R. Lester; James B. Reid (Journal of Plant Growth Regulation, 2001)

A Parametric Approach to Measuring Cerebral Blood Flow Autoregulation from Spontaneous Variations in Blood Pressure - David M. Simpson; Ronney B. Panerai; David H. Evans; A. Ross Naylor (Annals of Biomedical Engineering, 2001)

Organic carbon cycling in Taylor Valley, Antarctica: quantifying soil reservoirs and soil respiration - Melody B. Burkins; Ross A. Virginia; Diana H. Wall (Global Change Biology, 2001)
Summary Organic carbon reservoirs and respiration rates in soils have been calculated for most major biomes on Earth revealing patterns related to temperature, precipitation, and location. Yet data from one of the Earth's coldest, driest, and most southerly soil ecosystems, that of the McMurdo Dry Valleys of Antarctica, are currently not a part of this global database. In this paper, we present the first regional calculations of the soil organic carbon reservoirs in a dry valley ecosystem (Taylor Valley) and report measurements of CO 2 efflux from Antarctic soils. Our analyses indicate that, despite the absence of visible accumulations of organic matter in most of Taylor Valley's arid soils, this soil environment contained a significant percentage (up to 72%) of the seasonally unfrozen organic carbon reservoir in the terrestrial ecosystem. Field measurements of soil CO 2 ‐efflux in Taylor Valley soils were used to evaluate biotic respiration and averaged 0.10 ± 0.08 μmol CO 2 m −2 s −1 . Laboratory soil microcosms suggested that this respiration rate was sensitive to increases in temperature, moisture, and carbon addition. Finally, a steady‐state calculation of the mean residence time for organic carbon in Taylor Valley soils was 23 years. Because this value contradicts all that is currently known about carbon cycling rates in the dry valleys, we suggest that the dry valley soil carbon dynamics is not steady state. Instead, we suggest that the dynamic is complex, with at least two (short‐ and long‐term) organic carbon reservoirs. We also suggest that organic carbon in the dry valley soil environment may be more important, and play a more active role in long‐term ecosystem processes, than previously believed.

The Blodgett Plan: An Active-Management Approach to Developing Mature Forest Habitat - J. Sessions; D. Johnson; J. Ross; B. Sharer (Journal of Forestry, 2000)
A nonreserve-based landscape plan for developing mature forest habitat has been developed for the Blodgett Forest, one of the research forest properties of Oregon State University. Intended to provide a study and demonstration site for an alternative to fixed reserves, the plan calls for efficiently achieving and maintaining both mature forest and income. The forest goals include a mature forest acreage target, a mature forest landscape connectivity goal, a conversion time goal, and a net income goal. Spatial issues required development of a new harvest scheduling algorithm.

Selective effects on NGFI-A, MR, GR and NGFI-B hippocampal mRNA expression after chronic treatment with different subclasses of antidepressants in the rat - Lisa Bjartmar; Inga-Maj Johansson; Jan Marcusson; Svante B. Ross; Jonathan R. Seckl; Tommy Olsson (Psychopharmacology, 2000)

The Impact of Logging on Wildlife: A Study in Northeastern Pennsylvania - Todd S. Fredericksen; Brad D. Ross; Wayne Hoffman; Eric Ross; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson (Journal of Forestry, 2000)
Seeing and conserving wildlife are among the most important management objectives for nonindustrial private landowners in the eastern United States. Landowners want profitable timber harvests but also want to know how harvesting will affect their wildlife. The study examined associations between stand characteristics and wildlife abundance on 40 stands receiving different logging intensities in northeastern Pennsylvania and found that landowners have some choices when harvesting their stands for retaining or attracting different types of wildlife.

CONFIRMED SIGHTINGS OF DUSKY DOLPHINS ( LAGENORHYNCHUS OBSCURUS ) IN SOUTHERN AUSTRALIAN WATERS - Peter C. Gill; Graham J. B. Ross; William H. Dawbin; Hans Wapstra (Marine Mammal Science, 2000)

Comparative Effects of Ambient Ultraviolet‐B Radiation on Two Sympatric Species of Australian Frogs - Sara D. Broomhall; William S. Osborne; Ross B. Cunningham (Conservation Biology, 2000)
Declines have been observed in a number of Australian frog species, many of these at high elevations. Alpine regions in Australia are likely to be particularly subject to increases in ultraviolet‐B radiation ( UV‐B, 280–320 nm) because UV‐B levels increase with elevation and because anthropogenic depletion of ozone has been particularly severe in the southern hemisphere. We compared survivorship of embryos and tadpoles of a declining species of frog, Litoria verreauxii alpina , with those of a sympatric nondeclining species, Crinia signifera , under three ambient UV‐B treatments, unshielded, control, and UV‐B–excluding. Experiments were conducted in artificial water bodies established at three different elevations (1365, 1600, and 1930 m) in the Snowy Mountains of southeastern Australia. The exclusion of UV‐B significantly enhanced survival of L. v. alpina (declining species) at all elevations. Overall, the probability of dying was highest in the unshielded treatments and lowest under the UV‐B–excluding treatment for both species over all elevations. The probability of dying was significantly higher in L. v. alpina than in C. signifera for a given UV‐B treatment at the two highest elevations. Our results support the hypothesis that ultraviolet radiation is likely to be a contributing factor in the disappearance of L. v. alpina at high elevations in southern Australia.

Regioselective alkylation at the N4 positionof a 3-oxo-1,4-benzodiazepine on solid support - Fadia E. Ali; Catherine C.K. Yuan; Stephen T. Ross; Leon B. Hall (Molecular Diversity, 2000)

A high-temperature and high-pressure Raman spectroscopic study of CaGeO 3 garnet - T. D. Chaplin; N. L. Ross; B. Reynard (Physics and Chemistry of Minerals, 2000)

Relative Abundance and Species Richness of Herpetofauna in Forest Stands in Pennsylvania - Brad Ross; Todd Fredericksen; Eric Ross; Wayne Hoffman; Michael L. Morrison; Jan Beyea; Michael B. Lester; Bradley N. Johnson; Nell J. Fredericksen (Forest Science, 2000)
The relative abundance and species richness of herpetofauna was investigated to assess the impact of recent logging operations in 47 forest stands in northeastern Pennsylvania during 1996 and 1997. Stands including nonindustrial private forestlands and public lands that have received some type of harvesting within the last 8 yr ranged from near complete overstory tree cover to complete removal of overstory cover. Stands included the two dominant forest types in the region: northern hardwood (Betula, Fagus, Prunus, Acer, and Tsuga spp.) and oak-hickory/(Quercus and Carya spp.). A total of 8,181 individuals of 26 species (12 salamander, 7 snake, 6 frog, and 1 toad species) were observed in the study stands. The relative abundance and species richness of salamanders increased significantly with increasing retention of tree basal area. Forest stands containing > 15 m²/ha live tree basal area appeared to be a threshold level for high salamander abundance. Snake species abundance and richness increased significantly with increasing removal of tree basal area. The abundance of anuran species showed no significant relationship with amount of tree basal area removal, but the relative abundance and species richness of anurans depended on the presence of water within or bordering the stands. Forest type did not change the overall response of herpetofauna community composition to forest harvesting, although salamanders were more abundant in northern hardwood stands, and snakes were more abundant in oak-hickory stands. Patterns and threshold levels of abundance and species richness of herpetofauna determined in this study may be used to maintain the abundance and richness of selected species when harvesting forest stands. For. Sci. 46(1):139-146.

Growth limitation in young Euphausia superba under field conditions - Robin M. Ross; Langdon B. Quetin; Karen S. Baker; Maria Vernet; Raymond C. Smith (Limnology and Oceanography, 2000)
Growth rates of late furcilia and juvenile Antarctic krill ( Euphausia superba Dana) in the spring and summer were related to food quantity and quality. The 4 yr covered by this study (1991–1992, 1993–1994, 1994–1995, and 1995–1996) were part of the seasonal time series of the Palmer Long‐Term Ecological Research program. Chlorophyll a concentrations represented food quantity, and accessory photosynthetic pigments represented phytoplank‐ton community composition or food quality. Instantaneous growth rates reflected the in situ nutritional history of the previous intermolt period. The response of krill to the food environment was seen on temporal scales of days to weeks. Percent growth per intermolt period (percentage growth IMP −1 ( varied significantly both within and between years, ranging from ∼2 to 10% IMP −1 . Percent growth IMP −1 increased with increasing chlorophyll a (Chl a ), reaching a maximum of 9.3% IMP −1 above a critical concentration of about 3.5 mg m 23 . Maximum growth was reached in only 2 yr, 1991–1992 and 1995–1996. In a multiple regression analysis, total Chl a and prymnesiophyte‐Chl a explained over 71% of the temporal variance in growth. In general, highest growth was found toward the end of diatom blooms and lowest during periods of low phytoplankton biomass or blooms dominated by cryptophytes and prymnesiophytes. The results of this study support the hypothesis that maximum growth rates are only possible during diatom blooms and that production in Antarctic krill is limited by both food quantity and quality.

A General Method for Constrained Analysis of Fluorescence Anisotropy Decay: Application of the Steady-State Anisotropy - Edward L. Rachofsky; Barnabas Wolf; Carl N. Bialik; J. B. Alexander Ross; William R. Laws (Journal of Fluorescence, 1999)

Choosing a Forest Vision - Donald W. Floyd; Kelsey Alexander; Charles Burley; Arthur W. Cooper; Arthur DuFault; Ross W. Gorte; Sharon G. Haines; Bruce B. Hronek; Chadwick D. Oliver; Edward W. Shepard (Journal of Forestry, 1999)
It is unlikely, given the often-contentious history of the national forests, that incremental change in their administration can resolve fundamental differences in values. So concludes a task force appointed by the Society of American Foresters (SAF) to review federal forest management; its analysis and recommendations have been published in Forest of Discord: Options for Governing Our National Forests and Federal Public Lands. Whereas the Committee of Scientists was asked to stay within the framework of current laws and regulations, the SAF analysts were not so constrained. The following excerpts from Forest of Discord summarize the reasons that fundamental legislative and regulatory change is warranted and consider the purpose of having national forests and public lands.

CCG repeats in cDNAs from human brain - John J. Kleiderlein; Paul E. Nisson; Joel Jessee; W.-B. Li; K. G. Becker; Michael L. Derby; Christopher A. Ross; R. L. Margolis (Human Genetics, 1998)

Phenotypic variation of leaves and stems of wild stands of Cordyline australis (Lomandraceae) - Warwick Harris; Ross E. Beever; Peter B. Heenan (New Zealand Journal of Botany, 1998)
To determine whether there are geographical patterns in the phenotypic variation of wild populations of Cordyline australis (ti kouka, cabbage tree), stem size, and leaf size and shape were recorded for populations at 29 locations in New Zealand ranging from latitudes 34°27’ to 46°07'S and altitudes from 1 to 425 m. Correlations between stem and leaf variation and site and stand characteristics were examined. Stem diameter increased with increasing latitude and altitude. Leaf size dimensions and leaf shape ratios that defined differentiation of the petiole, and of leaf blade taper, also showed variation related to latitude. The phenotypic variation was predominantly continuous and followed environmental gradients that could have induced it. There was some local and regional discontinuity of phenotypic variation that was most apparent for stands in central‐eastern North Island.

Crystal structure of Escherichia coli manganese superoxide dismutase at 2.1-Å resolution - Ross A. Edwards; Heather M. Baker; M. M. Whittaker; James W. Whittaker; Geoffrey B. Jameson; E. N. Baker (JBIC Journal of Biological Inorganic Chemistry, 1998)

DNA Adduct Formation by the Pesticide Alachlor and Its Metabolite 2-Chloro-N-(2,6-diethylphenyl)acetamide (CDEPA) - G. B. Nelson; J. A. Ross (Bulletin of Environmental Contamination and Toxicology, 1998)

Approximate Analytical Solution of the Nonlinear Diffusion Equation for Arbitrary Boundary Conditions - J.-Y. Parlange; W. L. Hogarth; M. B. Parlange; R. Haverkamp; D. A. Barry; P. J. Ross; T. S. Steenhuis (Transport in Porous Media, 1998)

Cytological characterization of four meiotic mutants of Arabidopsis isolated from T-DNA-transformed lines - K. J. Ross; P. Fransz; S. J. Armstrong; I. Vizir; B. Mulligan; F. C. H. Franklin; G. H. Jones (Chromosome Research, 1997)

Functional motifs in the IgH enhancer of the channel catfish - B. G. Magor; David A. Ross; Darlene L. Middleton; Gregory W. Warr (Immunogenetics, 1997)

Polyandry in the genus Apis , particularly Apis andreniformis - B. P. Oldroyd; Morag J. Clifton; Siriwat Wongsiri; Thomas E. Rinderer; H. Allen Sylvester; Ross H. Crozier (Behavioral Ecology and Sociobiology, 1997)

Relationships between NADPH diaphorase staining and neuronal, endothelial, and inducible nitric oxide synthase and cytochrome P450 reductase immunoreactivities in guinea-pig tissues - H. M. Young; Anna J. O'Brien; John B. Furness; Daniela Ciampoli; James P. Hardwick; Timothy J. McCabe; Ramani Narayanasami; Bettie Sue S. Masters; W. Ross Tracey (Histochemistry and Cell Biology, 1997)

Levels of polyandry and intracolonial genetic relationships in Apis florea - B. P. Oldroyd; Adam J. Smolenski; Jean-Marie Cornuet; Siriwat Wongsiri; Arnaud Estoup; Thomas E. Rinderer; Ross H. Crozier (Behavioral Ecology and Sociobiology, 1995)

Parsnip yellow fleck and rice tungro spherical viruses resemble picornaviruses and represent two genera in a proposed new plant picornavirus family (Sequiviridae) - B. Reavy; M. A. Mayo; A. D. Turnbull-Ross; A. F. Murant (Archives of Virology, 1993)

Primary irritant contact dermatitis from synthetic pyrethroid insecticide exposure - Stephen A. Flannigan; Stephen B. Tucker; Marcus M. Key; Charles E. Ross; Edward J. Fairchild; Barbara A. Grimes; Ronald B. Harrist (Archives of Toxicology, 1985)

Sibling manipulation and indirect fitness in termites - Ross B. Zimmerman (Behavioral Ecology and Sociobiology, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Induction of null-activity mutants for the acid phosphatase-1 gene in Drosophila melanogaster - John B. Bell; Ross J. MacIntyre; Allan P. Olivieri (Biochemical Genetics, 1972)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

The effect of immersion in sea water on the sprouting of potato tubers - J. I. G. Ross; D. B. Robinson (American Journal of Potato Research, 1954)